SISTEM PENDUKUNG KEPUTUSAN HUKUM PEMBAGIAN HARTA WARISAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Saputra, Yogi; Sulindawaty, Sulindawaty (STMIK Kaputama, 2019)
Islamic inheritance law regulates the transfer of property from someone who has died to the living. The rules regarding the transfer of assets are called by various Names. Basically, inheritance law in Islam applies to all Muslims throughout the world. Nevertheless, the style of an Islamic state and life in that country or region have a different influence on inheritance law, this is due to several factors. In inheritance law there is a possibility of differences of opinion among the legal experts themselves, especially regarding the verses that allow for more interpretation. In addition, there are limited experts or people who have special knowledge and expertise who can provide solutions to people who need information about the distribution of inheritance. Decision support systems can be used as a solution to a problem or for an opportunity. Decision Support System (SPK) is used in decision making. Decision support system (SPK) uses the term CBIS (Computer Based Information system) which is flexible, interactive, and adaptable, developed to support each solution of specific unstructured management problems. The basic concept of the Simple Additive Weighting method is to find the weighted sum of the performance ratings for each alternative on all attributes. the process of normalization of the decision matrix into a scale that can be compared with all existing alternative ratings so that it can be applied in solving various kinds of case calculations